Intramarrow penetration synergized with advanced platelet-rich fibrin in periodontal regeneration: A randomized controlled trial - Parth Sharma; R G Shiva Manjunath; Shiva Shankar Gummalur; Lavanya Kunche (Journal of Indian Society of Periodontology, 2023)
Background: Intramarrow penetration (IMP) is one of the recent treatment protocol where decortication is performed to stimulate osteogenic cells. IMP improves the blood supply and the inherent osteogenic properties of the vital bone and has the advantages of minimal surgical invasion, time, and cost. Incorporation of IMP in the regeneration of periodontal defects is very scarce. Hence, the present study aimed to evaluate the involvement of IMP and advanced platelet-rich fibrin (A-PRF) in the regenerative outcomes in the treatment of intrabony defects. Materials and Methods: In the present randomized controlled trial, 20 periodontitis patients with 20 defects were randomly allotted into two groups: group I open flap debridement (OFD) and A-PRF, group II OFD, intramarrow debridement, and A-PRF. Clinical parameters recorded were plaque index (PI), gingival index (GI), and clinical attachment level (CAL) probing depth. Radiographic parameters were defect depth, defect resolution, and change in alveolar crest height. Values were tabulated and subjected to statistical analysis. Paired and unpaired t-tests were performed for intra and intergroup comparisons. P <0.05 was set as statistically significant. Results: Intragroup comparisons showed a significant reduction (P < 0.05) in probing pocket depth, GI, PI, gain in CAL, and greater bone fill in both the groups from baseline to 6 months postoperative. Intergroup comparisons were not statistically significant (P > 0.05). Conclusion: Within limitations, both treatment modalities stand good, but utilization of IMP along with A-PRF results in effective regenerative outcome in intrabony defects because of its stimulation of osteogenic properties.